Development of Mini-Barcode Based on Chloroplast Genome and Its Application in Metabarcoding Molecular Identification of Chinese Medicinal Material Radix Paeoniae Rubra (Chishao) - Yang, Xia; Yu, Xiaolei; Zhang, Xiaoying; Guo, Hua; Xing, Zhimei; Xu, Liuwei; Wang, Jia; Shen, Yuyan; Yu, Jie; Lv, Pengfei; Wang, Yuefei; Liu, Mengyang; et al. (Frontiers in Plant Science, 2022)
Radix Paeoniae Rubra, also known as Chishao, is a typical multi-origin Chinese medicinal material. There are differences in chemical composition and efficacy among different Chishao species. Therefore, accurate identification of original species is of great significance for Chishao. In this study, the chloroplast genome sequences of Paeonia lactiflora and Paeonia veitchii were obtained by next-generation sequencing (NGS) technology, and then the hypervariable regions were selected to design two mini-barcode candidates for species identification. Combined with DNA metabarcoding technology, we performed qualitative and quantitative analysis on the artificially mixed samples of P. lactiflora and P. veitchii and evaluated the identification ability of these mini-barcode candidates. Furtherly, the mini-barcode with good performance was applied to distinguish the Chinese patent medicine “cerebral thrombosis tablets” containing Chishao. The results showed that the chloroplast genomes of P. lactiflora and P. veitchii were 152,750 bp and 152,527 bp, respectively. They exhibited a typical quadripartite structure including a large single-copy region (LSC), a small single-copy region (SSC) and a pair of inverted repeat regions (IRs). The nucleotide polymorphism analysis revealed seven variable protein-coding regions as petL, psaI, psbJ, rpl16, ycf1b, psaC, and ndhF, and two mini-barcodes were developed from ycf1b and ndhF respectively. The experiment on artificial mixtures showed that both two mini-barcodes have qualitative identification capabilities. Besides, the result showed that P. lactiflora was the only raw material of Chishao in all collected “cerebral thrombosis tablets” samples. In general, this study has established a method to realize the qualitative and quantitative identification of Chishao as multi-origin Chinese medicinal materials, which can be applied to Chinese patent medicines containing Chishao.